The Impact of Husband`s Early Retirement on Marital Adjustment – Empirical Study on Retired People in Saudi Airlines in Jeddah During 1441 AH – - Makki, Hanaa Mohammed (Journal of Humanities & Social Sciences, 2020)
This Study Aimed to Investigate the Impact of Husband Early Retirement On Marital Adjustment, And The Study Has Been Applied On a Group of Early Retired Saudi Airlines Employees Aged Between 45 – 57 Years Old in Jeddah Governorate, The Sample Consisted of 100 Individuals of Both Males and Females (Early Retired Husbands and Their Wives). And It Has Been Used Descriptive Analytical Approach on A Selected Purposive Sample, And The Study Has Been Conducted During the Second Term of the Scholastic Islamic Calendar Year, 1441. It Has Been Used Questionnaire as A Study Tool. The Study Reached Many Results Including That the Nature of Relationship Among More Than One-Third of the Sample of Both Males and Females Has Changed Somehow to Be Better Than Before After Early Retirement, And The Early of Husband Retirement Positively Impacts the Marital Adjustment for Both Husbands and Wives. In Light of the Results of the Study, Some Recommendations Were Presented, Including That the Study Should Be Applied on Substantial Sample of Society’s Members of Early Retirement Whether They Are Military or Civil.